2020
DOI: 10.1108/ijbm-07-2019-0269
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of adoption and continuance intentions toward Internet-only banks

Abstract: PurposeThe purpose of this study is to investigate the determinants of consumers' intention to adopt or continue to use Internet-only banks based on the benefit–risk framework and network externality theory. It also examines the difference in the determinants between pre- and postadoption stages of innovation.Design/methodology/approachThe proposed research model was tested by using online survey data collected from a South Korean sample, which was divided into two subgroups of 321 nonadopters and 351 existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
106
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(120 citation statements)
references
References 61 publications
10
106
4
Order By: Relevance
“…Both of these approaches arguably facilitate banking anytime, anywhere. This, in turn, highlights the elements of convenience and economic efficiency that have been found to have positive effects on consumer's adoption intention and continuance intention of digital services (Lee & Kim 2020) to hold true in a South African context too.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Both of these approaches arguably facilitate banking anytime, anywhere. This, in turn, highlights the elements of convenience and economic efficiency that have been found to have positive effects on consumer's adoption intention and continuance intention of digital services (Lee & Kim 2020) to hold true in a South African context too.…”
Section: Resultsmentioning
confidence: 68%
“…Internet-or digital-only banks offer alternative approaches to online transacting and banking by making services available exclusively through online channels (websites) or by means of smartphone apps, thereby challenging traditional banking business models by eliminating the need to establish and maintain physical bank branches. Technology has fundamentally altered the creation, delivery, reception and utilisation of these financial products (Pyun et al 2002), with convenience and economic efficiency already having had positive effects on consumers' adoption intention and continuance intention of international digital-only banks (Lee & Kim 2020).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…It is commonly believed that banks which addressed all features of e-banking are likely to achieve better performance, enhance efficiency and improve on service quality (Robinson, 2000). According to Lee & Kim (2020), banks should decrease protection risks and increase consumer confidence through better security measures and more sophisticated electronic offerings. On this note, many banks have quickly realised that a significant number of customers are likely to use e-banking as they offer many advantages for banks, including the reduction of cost on physical structures.…”
Section: E-bankingmentioning
confidence: 99%
“…The results revealed that convenience was positively related to the intention to continue using the personal digital assistants. Based on the benefit-risk framework and network externality theory, Lee and Kim (2020) proposed a research framework to investigate the key antecedents influencing consumers' intention to use or continue to use Internet-only banks. The results revealed that convenience experienced in the post-adoption stage exerted a positive effect on consumer's willingness to continue to use.…”
Section: Theoretical Background and The Development Of Hypothesesmentioning
confidence: 99%
“…Five items measuring PEOU were adapted from Venkatesh (2000) and Cho & Sagynov (2015), while PU was based on Davis (1989) & Morosan (2014. Convenience was measured with four items based on Lee and Kim (2020).…”
Section: Continuance Intentionmentioning
confidence: 99%